Mothers' Cognitive References to 2‐Year‐Olds Predict Theory of Mind at Ages 6 and 10. Issue 3 (9th December 2013) - Ensor, Rosie; Devine, Rory T.; Marks, Alex; Hughes, Claire
<x xml:space="preserve">Abstract</x> Mothers' mental‐state references predict individual differences in preschoolers' false‐belief (FB) understanding; less is known about the origins of corresponding variation in school‐age children. To address this gap, 105 children completed observations with their mothers at child ages 2 and 6, three FB tasks and a verbal comprehension test at age 3, and five FB tasks at age 6. Seventy‐seven of these children completed five Strange Stories at age 10. Individual differences in mothers' cognitive references at child age 2 predicted variation in children's FB understanding at age 6 and Strange Stories scores at age 10 (controlling for number of mothers' turns and children's mental‐state references, verbal comprehension and FB understanding at age 3, and mothers' cognitive references at child age 6).